Limits of analytical vector measures - Romanov , V. A. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The article attempts to determine when a vector measure is the limit of a sequence of analytic vector measures in the sense of convergence in semivariation and when it is the limit of a sequence of such measures in variation.